Indicating Quality of Place for station precinct development: Enhancing ‘place’ in the place/node model - Duckworth-Smith, A.; Babb, Courtney (2015)
Transit Oriented Development (TOD), essentially the aggregation of urban activity and development around nodes in a public transport network, has been a strategic objective of many cities for at least two decades. Over a similar timeframe Bertolini’s (1999) node-place model has been used to investigate the performance of these locations in this respect. The model identifies an optimal ‘balanced’ state where transport and land use functionality of station precincts are relatively even and TOD objectives could be said to be met. Unbalanced states indicate a latent potential toward achieving this desired objective. In practice the actualisation of this potential relies on a complex range of factors. Is it possible however to identify these factors in relation to the desired objective? Such knowledge could assist in guiding both public and private investment toward achieving TOD, making more efficient use of available resources. This research focuses on one aspect of this problem, identifying the underlying spatial qualities of place of precincts which would seem to be important in influencing their development towards TODs. An analytical framework is developed to achieve this and then applied to 13 passenger rail station precincts in the Perth Metropolitan area which allows a preliminary assessment of its validity for future application. This research has been undertaken as part of a broader research project initiated by the Planning and Transport Research Centre (PATREC) investigating the transport and land use characteristics of station precincts located within freeway medians in Perth.